2009
DOI: 10.1186/1471-2288-9-65
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for improving patient recruitment to focus groups in primary care: a case study reflective paper using an analytical framework

Abstract: BackgroundRecruiting to primary care studies is complex. With the current drive to increase numbers of patients involved in primary care studies, we need to know more about successful recruitment approaches. There is limited evidence on recruitment to focus group studies, particularly when no natural grouping exists and where participants do not regularly meet. The aim of this paper is to reflect on recruitment to a focus group study comparing the methods used with existing evidence using a resource for resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 39 publications
0
25
0
6
Order By: Relevance
“…In a national multi-center epilepsy trial in New Zealand, researchers developed a website to facilitate subject recruitment and data collection (10). As community based research becomes more common, electronic data can aid recruitment in primary care settings (11,12) given the appropriate privacy controls (13). McGregor and associates (14) describe the use of an algorithm to identify potential study participants using primary care data to select patients based on the trial’s inclusion and exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…In a national multi-center epilepsy trial in New Zealand, researchers developed a website to facilitate subject recruitment and data collection (10). As community based research becomes more common, electronic data can aid recruitment in primary care settings (11,12) given the appropriate privacy controls (13). McGregor and associates (14) describe the use of an algorithm to identify potential study participants using primary care data to select patients based on the trial’s inclusion and exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…El muestreo intencional, en oposición al muestreo probabilístico que prioriza la equiprobabilidad de los participantes, selecciona casos ricos en información. Investigaciones recientes demuestran la eficacia del muestreo intencional en los estudios cualitativos (Dyas, 2009).…”
Section: Metodologíaunclassified
“…Recruiting and retention of participants to large-scale longitudinal studies has become a challenge in recent years [ 1 ], particularly when resources are limited and low response rates lead to the costs of more traditional random sampling methods becoming prohibitive [ 2 ]. Qualitative inquiries with members of the target population can assist in the development of effective recruiting techniques [ 3 ]. The current study utilized qualitative methods to examine the facilitators and barriers to participation in a national cohort online survey study of women aged 18-23 years.…”
Section: Introductionmentioning
confidence: 99%
“…Existing qualitative research has indicated a number of factors that encourage participation in health research and how to maximize recruitment. Demonstrating the importance of remaining alert during the recruitment phase, Dyas et al reported upon recruitment to a focus group study as part of a primary care sleep intervention in the United Kingdom [ 3 ]. While monitoring the recruitment of participants into the focus groups, the authors noted evidence of recruitment tactics not in keeping with the original research plan, and a number of changes were necessary to their original recruitment strategy to boost lagging participation numbers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation